Increased neutrophil lymphocyte ratio and platelet lymphocyte ratio in malignant parotid tumors - Kuzucu,İhsan (2020)
Abstract Introduction Recently it has been reported that a high preoperative neutrophil-lymphocyte ratio and platelet-lymphocyte ratio may be related to increased recurrence risk, tumor aggressiveness, and worsened prognosis in various malignancies. Objective The objective of this research is to explore whether neutrophil-lymphocyte ratio and platelet-lymphocyte ratio in parotid tumors may or may not be used as a cancer marker. Methods This retrospective research has been conducted on a total of 228 patients consisting of 83 healthy persons and 145 patients with a mass in the parotid gland, who applied to a tertiary referral center and underwent surgery. Patients have been divided into two groups by their histopathological findings as malignant or benign parotid tumor. A third group consisting of healthy people has been defined as the control group. Also the malignant parotid tumor group has been divided into two subgroups as early stage and advanced stage. The groups have been compared in terms of neutrophil-lymphocyte ratio, platelet-lymphocyte ratio and other laboratory data. Results The average neutrophil-lymphocyte ratio values of malignant parotid tumor, benign parotid tumor, healthy control groups were 2.51, 2.01, 1.79 respectively and the difference was statistically significant (p < 0.001). There was no significant difference between advanced stage and early stage parotid tumor groups in terms of average neutrophil-lymphocyte ratio value (p = 0.782). In dual comparisons, the platelet-lymphocyte ratio value of patients in the malignant group was found out to be statistically significantly higher than that of benign and control groups (p < 0.001 and p = 0.001 respectively). Conclusion To the best of our knowledge our research is the first in the medical literature comparing neutrophil-lymphocyte ratio and platelet-lymphocyte ratio in patients with parotid tumor. neutrophil-lymphocyte ratio and platelet-lymphocyte ratio can serve as cost-effective, repeatable, easily accessible, and helpful inflammatory markers in order to distinguish patients with malignant parotid tumor from healthy people.